Risk Assessment of Shield Tunnel Construction in Karst Strata Based on Fuzzy Analytic Hierarchy Process and Cloud Model - Guowang Meng; Yangchun Ye; Bo Wu; Guijun Luo; Xu Zhang; Zhiqiang Zhou; Wentao Sun (Shock and Vibration)
Karst is an unfavorable geology that is very undesirable in tunnel construction. It is extremely risky due to the complexity and fuzziness of shield excavation in karst strata. To reduce the construction risk of shield tunneling in karst strata, a risk assessment method based on cloud model and fuzzy analytic hierarchy process (FAHP) is proposed. A risk assessment index system is established, including four first-level indices of karst geological conditions, hydrogeological conditions, tunnel design, and shield construction, as well as seventeen second-level indices. Fuzzy analytic hierarchy process is used to determine the evaluation indices weights. The numerical characteristics of each index and the risk cloud diagram are obtained via the backward cloud generator and forward cloud generator, respectively. The certainty degrees of the assessment indices corresponding to each risk level are calculated, and the final risk level is determined based on the comparison of the risk cloud diagram and the principle of maximum certainty. The proposed model is applied to the risk analysis and calculation of shield tunnel engineering, and the risk assessment results indicate that the comprehensive risk level of shield tunnel construction in karst strata is level II, which is consistent with the actual project. It demonstrates that the proposed method can provide a reference for the risk assessment of shield tunnels construction in karst strata.